2013
DOI: 10.1089/cbr.2012.1357
|View full text |Cite
|
Sign up to set email alerts
|

Human Prostate Stem Cell Antigen and HSP70 Fusion Protein Vaccine Inhibits Prostate Stem Cell Antigen-Expressing Tumor Growth in Mice

Abstract: Prostate stem cell antigen (PSCA) has been considered a potentially worthwhile target for prostate cancer therapy with its overexpression in both androgen-dependent and androgen-independent prostate cancers. However, PSCA is an autoantigen that can evoke immunological tolerance and hardly incite effective immunologic response. In this study, we sought to construct the fusion protein vaccines based on PSCA and heat shock protein 70 (HSP70) and to evaluate their immune responses and therapeutic efficacy. A serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…PCa has, like most cancers, an immunosuppressive tumor microenvironment. Dong et al found that immunization with PSCA protein could incite effective immunologic response, which inhibited the growth of PSCA expressing tumors and prolonged the survival time of mice.…”
Section: Discussionmentioning
confidence: 99%
“…PCa has, like most cancers, an immunosuppressive tumor microenvironment. Dong et al found that immunization with PSCA protein could incite effective immunologic response, which inhibited the growth of PSCA expressing tumors and prolonged the survival time of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Hsp70 with established pro‐survival functions, the role of Hsp60 is more controversial with both pro‐survival and pro‐apoptotic functions reported . Several studies have focused on the implications of Hsp60 and Hsp70 during human prostate tumourigenesis and cancer progression, as well as on their usefulness as prognostic markers of PCa . The information obtained from these studies may provide the scientific basis for the design of antitumour treatments targeting HSPs in combination with conventional therapies, which could improve the survival of PCa patients in the next future .…”
Section: Introductionmentioning
confidence: 99%
“…Although no relevant vaccination has been approved for clinical application, numerous studies have demonstrated robust anti-tumor effects of various types of vaccines that contain HSP70, effectively stimulating cellular or even humoral immune responses. Peptide-based vaccines are relatively easy to manufacture and usually composed of the HSP70 protein integrated with tumor-associated antigens (TAAs) or tumor-specific antigens (TSAs), such as melanoma-associated antigen gene (MAGE)-HSP70 (164-167), prostate stem-cell antigen (PSCA)-HSP70 (168), and Mela-HSP70 (169). Two studies produced a promising human papillomavirus 16 (HPV16) protein vaccine of E7-HSP70 that robustly induces E7-specific CD8 + T cell immune response and resulted in significant prophylactic and therapeutic effects against E7-expressing cervical cancer (170,171).…”
Section: Developing Hsp70-based Vaccinesmentioning
confidence: 99%